Clinical Profile and Management of Rheumatic Heart Disease in Children and Young Adults at a Tertiary Cardiac Center in Indonesia - Lilyasari, Oktavia; Prakoso, Radityo; Kurniawati, Yovi; Roebiono, Poppy S.; Rahajoe, Anna Ulfah; Sakidjan, Indriwanto; Harimurti, Ganesja M. (Frontiers in Surgery, 2020)
Introduction: Rheumatic heart disease (RHD) remains a major public health issue affecting children and young adults in developing countries. This study aimed to evaluate the clinical characteristics, management, and reactivation of RHD among children and young adults. Patients and Methods: This was a hospital-based retrospective study conducted at the National Cardiovascular Center Harapan Kita, Indonesia; we retrieved relevant data from patients diagnosed with RHD between 2012 and 2018. Results: Two hundred and seventy-nine patients were diagnosed with rheumatic heart disease, of whom 108 were children (mean age of 12.02 ± 3.36 years) and 171 were young adults (mean age was 24.9 ± 3.84). RHD was more common in female than in male young adults (1.5:1). Hospitalization due to RHD complications such as congestive heart failure was seen in 11.11% of cases in children, while pulmonary hypertension was present in 19.95% young adult cases. Reactivation of RHD occurred in 17.2% (48/279) cases, significantly in children (p < 0.001). Overall, the mitral valve (either isolated or combined) was the organ most affected in children (39.13%) and young adults (44.81%). Isolated mitral regurgitation was more common in children (13/21, 61.9%), while isolated mitral stenosis was more common in young adults (19/47, 40.42%). There was a high rate of rheumatic tricuspid valve disease in all populations (193/279, 69.17%) and reported involvement of pulmonary regurgitation (46/279, 16.48%). Multivalve lesions were more common than single lesions in both groups, with a combination of mitral and tricuspid regurgitation the predominant type in children (32/43, 74.41%) and mixed mitral lesion and tricuspid regurgitation in young adults (22/72, 30.56%). We observed a significant occurrence of quadrivalve lesions in children (p = 0.039). Valve repair was more common in children (49.07%) and replacement in young adults (32.16%), with low in-hospital mortality. Compliance with secondary prophylaxis was a significant challenge. Conclusion: Chronic RHD often presented with complications of the disease or reactivation of rheumatic fever (RF). Inadequate treatment of RF/RHD leads to extensive valvular damage and consequent disabilities. Efforts toward active early diagnosis and prompt treatment of RF/RHD and effective preventive measures are essential.